Relationship Analysis Economic Growth and Unemployment Rate in East Java: Okun's Curve Anomaly Before and After the COVID-19 Pandemic: Analisis Hubungan Pertumbuhan Ekonomi dan Tingkat Pengangguran di Jawa Timur: Anomali Kurva Okun Sebelum dan Sesudah Pandemi COVID-19 - Suprianto Suprianto; Muchammad Luthfi Affandy; Royhan Faradis; Muhamad Maulana Musafir (Universitas Muhammadiyah Sidoarjo, 2026)
Economic growth and unemployment rates are two macroeconomic indicators used to measure the government's success in improving the welfare of the people. Low economic growth will lead to high unemployment rates, which is in line with Okun's law. Over the past two years, East Java's economic growth has contracted but has not been accompanied by a decline in unemployment rates. This is interesting considering that reality does not align with theory. This study aims to examine the consistency of Okun's law with reality both before and after the COVID-19 pandemic. What is interesting about this study is that the COVID-19 pandemic has significantly changed the economy of East Java. This reality has actually improved the relationship between economic growth and unemployment rates. Based on Pearson's correlation coefficient, an inverse relationship was found between the pre- and post-pandemic periods. Therefore, it can be concluded that external interventions such as a pandemic can improve the relationship between the two variables to an appropriate level. The implications of these findings indicate that post-pandemic economic recovery needs to be directed towards strengthening labour-intensive sectors that absorb a large workforce. Policies to develop MSMEs, downstreaming, and improving skills after the pandemic could be the key to making East Java's economic growth more inclusive while reducing unemployment. Highlights: Tests Okun’s law consistency in East Java before and after COVID-19. Finds inverse correlation between growth and unemployment post-pandemic. Recommends post-pandemic recovery through labour-intensive and MSME sectors. Keywords: Economic Growth, Open Unemployment Rate, Okun's Curve, Pandemic, Pearson